ISLAMIC RESPONSES TO GLOBAL CRISIS: THE ROLE OF FAITH IN ADDRESSING MODERN ISSUES - Dr. Khanzada Muhammad Waqar; Safia Khan; Dr. Mufti Muhammad Iltimas Khan* (Journal of Religion and Society, 2024)
The contemporary world faces a multitude of crises, ranging from economic instability, environmental degradation, and socio-political turmoil to ethical dilemmas and humanitarian challenges. In addressing these global concerns, faith-based approaches, particularly those rooted in Islamic teachings, offer valuable perspectives on crisis management and sustainable solutions. Islam, as a comprehensive belief system, integrates ethical, economic, environmental, and social justice principles that can provide holistic responses to modern challenges. Key concepts such as zakat (charity), khilafah (stewardship), and justice-oriented economic principles offer alternative frameworks for equitable resource distribution, environmental sustainability, and financial resilience. Additionally, Islamic teachings advocate for compassion, social responsibility, and community engagement, which are essential in mitigating the adverse effects of crises. Through an analysis of Islamic economic principles, environmental ethics, and social justice perspectives, this study explores the role of faith in fostering global resilience. Furthermore, case studies highlight practical applications of Islamic responses to specific global crises, demonstrating the adaptability and efficacy of faith-driven solutions. Ultimately, the findings emphasize the significance of integrating Islamic moral frameworks into contemporary crisis management strategies to promote ethical governance, equitable development, and sustainable progress. Keywords: Islam, Global Crisis, Faith-Based Response, Islamic Ethics, Social Justice, Sustainability, Zakat, Khilafah, Islamic Finance, Environmental Ethics.